Ellis-van Creveld syndrome: a case report - Marya Hameed,; Jesrani, Ameet Kumar; Syed Maaz Tariq,; Hanif, Hina; Bansari, Suneeta; Kumar, Ashok (Journal of the Pakistan Medical Association, 2024)
Ellis-van Creveld syndrome (EVC), also known as chondroectodermal dysplasia, is a rare entity. It most commonly affects the tubular bones leading to dwarfism and a long trunk with ossification defects. Other presentations are wide hands and feet, dysplastic nails, thin hair, and cardiac malformations. An eight-year-old female patient presented to our tertiary care centre with complaints of short stature, abnormal dentition, and fatigue. The child’s parents were first-degree relatives. On radiological imaging, it was revealed that the patient had postaxial polydactyly, short stature, and genu valgum deformity along with mild cardiomegaly. All these features were indicative of Ellis-van Creveld syndrome. EVC is a rare clinical syndrome with a distinctive clinical presentation. It requires comprehensive radiological investigations and the management is best done with a multidisciplinary approach. Keywords: Cardiomegaly, Polydactyly, Ellis-van Creveld Syndrome.